Komparasi Self-Efficacy Guru Matematika dan Guru Madrasah Aliyah Negeri (MAN) Kota Banjarmasin - Qamaruzzaman, Muhammad; Hermina, Dina; Huda, Nuril (STKIP PGRI SITUBONDO, 2024)
This research is a comparative study of the Self Efficacy of Mathematics teachers with Madrasah Aliyah Negeri (MAN) teachers in the city of Banjarmasin. The sample was taken randomly from 36 Mathematics teachers, while there were 71 MAN teachers from Banjarmasin City. Meanwhile, the research instrument is a questionnaire. The results of the research show that the self-efficacy of Mathematics teachers and MAN teachers in Banjarmasin city is descriptively both high, but in terms of percentage there is a significant difference of 2.95%. The self-efficacy of MAN teachers in Banjarmasin city was higher than Mathematics teachers in Banjarmasin city